Analysis of procurement of raw materials and income of tapioca flour at PT. Hutahaean Pintu Bosi Village Laguboti Sub-district - Maju Lubis; Reswita Reswita; Sriyoto Sriyoto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This research was conducted in December 2019 - January 23, 2020 at PT. Hutahaean Pintu Bosi Village Laguboti District Toba Samosir Regency North Sumatra Province. This research aims to find out the procurement of raw materials in PT. Hutahaean, to find out the number of EOQ, Safety Stock, ROP and TIC in PT. Hutahaean, and to find out the income of tapioca flour in PT. Hutahaean. The data used in this study is primary and secondary data. Primary data is obtained from live interviews with respondents using a list of questions or questionnaires. Secondary data in the form of supporting data in this study from previous research results or books and literature relevant to this study. The analysis used is inventory analysis by EOQ method, Safety Stock (SS), Reorder Point (ROP), Total Inventory Cost (TIC), and revenue analysis. The result of this study is procurement of raw materials has 2 sources namely from farmers and core gardens with an average monthly amount of 1.305,62 tons and 125,23 tons, safety stock per month of 55,03 tons, for optimal purchase of raw materials with EOQ method of 232,34 tons with the frequency of purchase 6 times in 1 month, the number of rebookings or ROP of Rp.110,07 tons, TIC according to PT. Hutahaean amounted to Rp. 12.583.225 while TIC according to EOQ amounted to Rp. 10.222.978,24 and Average receipts amounted to Rp. 2.155.351.605 per month, the average total cost was Rp. 1.449.957.057 per month and the average income was Rp. 705.394.548 per month.